EFEKTIVITAS PENGAWASAN DEWAN PENGAWAS SYARIAH (DPS) TERHADAP OPERASIONAL BANK SYARI’AH - Rohmaniyah, Rohmaniyah; Zandra, Rosy Aprieza Puspita (JURNAL AKUNTANSI DAN INVESTASI, 2016)
In this study, there are three research focus into the main study. First, how do DPS oversight mechanisms. Second, what are the factors supporting and inhibiting DPS supervision. Third, how the effectiveness of the supervision of DPS PT. Prima Sarana Mandiri Pamekasan. This study uses a qualitative approach with descriptive. Data source obtained through interviews and documentation. The results of this study indicate that in overseeing new product there are several steps being taken by the DPS, namely: first, DPS asked for an explanation to the board of directors of the new products that will be issued. Second, check if the new product in accordance with Islamic principles. Third, give an opinion on the sharia new product. In determining the effectiveness of the supervision of DPS, there are three things that made any indication, that is the way DPS oversight, supporting factors and obstacles as well as supervision of DPS output. How do DPS supervision in PT. SRB Sarana Prima Mandiri are in accordance with the system of supervision that have been defined in the SEBI (Circular Letter of BI), ways are also aided by the many contributing factors that facilitate DPS oversight. In terms of output, there were no operational products and products that come out of the principles of sharia, so the conclusion DPS oversight conducted in PT. SRB Sarana Prima Mandiri declared effective